The influence of the store atmosphere towards consumer attitudes on Hypermart stores - Gebby Maurizka Lembah; Jony Oktavian Haryanto (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
The aim of this study is to examine how store atmosphere can influence Hypermart consumers’ satisfaction, which then forms a repurchase intention and generates word of mouth. This study used data from 170 respondents obtained using the Purposive Sampling technique. The research data were analyzed using the Structural Equation Modeling (SEM) method with Lisrel 8.8 software. The results showed that music had a positive influence on store atmosphere and word of mouth. In addition, the store atmosphere has a positive influence on consumer satisfaction and repurchase intention. Afterward, consumer satisfaction has a positive influence on repurchase intention, and repurchase intention has a positive influence on word of mouth. The managerial implication in this study is that marketers should create an attractive store atmosphere to achieve consumer satisfaction to make consumers interested in repurchasing and in an effort to retain consumers to continue to generate abundant profits.